Place-based Policies and Household Wealth in Africa - Matthew Amalitinga Abagna; Cecília Hornok; Alina Mulyukova (Journal of Development Economics, 2025)
This paper provides novel evidence on the impact of a prominent place-based policy – Special Economic Zones (SEZs) – on the economic well-being of African households. Exploiting time variation in SEZ establishment on a dataset of repeated cross-sections of households in 10 African countries during 1990-2020, we show that households living near SEZs become wealthier relative to the national average after SEZ establishment. The effect accrues mostly within 10 km of SEZs, is not driven by selective migration, and is accompanied by improved access to household utilities, higher consumption of durable goods, increased educational attainment and a shift away from agricultural activities.
Keywords: F6; F21; O15; O25; 330; Special economic zone; Place-based policy; Household wealth; Africa